DOI: 10.14264/uql.2020.79
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the growth of III-V semiconductor nanowires with component addition in metal-organic chemical vapor deposition

Abstract: In recent decades, extensive research has been engaged into III-V semiconductor nanowires. It has been widely recognized that they have promising applications for electronic and optoelectronic devices due to their intrinsic material and unique geometry.Currently, the controllable growth of binary III-V nanowires can be achieved via Au-catalysed vapor-liquid-solid method in both metal organic chemical vapor deposition (MOCVD) and molecular beam epitaxy (MBE) system. Conventionally, the key parameters for tuning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Finally, the evacuation of the second precursor is performed using inert gas which marks the end of the process. 99 Although, the precursor does not require etching of the prevailing oxides, with high purity, volatile, no disintegration, no gas phase reaction, and must be non-toxic. Good quality film, low contamination and better electrical properties can be produced by thermal and plasma enhanced ALD.…”
Section: Common Deposition Methods Of Gate Oxide Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the evacuation of the second precursor is performed using inert gas which marks the end of the process. 99 Although, the precursor does not require etching of the prevailing oxides, with high purity, volatile, no disintegration, no gas phase reaction, and must be non-toxic. Good quality film, low contamination and better electrical properties can be produced by thermal and plasma enhanced ALD.…”
Section: Common Deposition Methods Of Gate Oxide Filmsmentioning
confidence: 99%
“…Due to the growth mechanism constraints of the precursors, there is uniform coverage over intricate shapes. 98,99 The effect of CVD on the properties of deposited films on a SiC substrate was studied by Guo et al 100 They observed the epitaxial growth of graphene/ epitaxial-SiC on Si. The crystal quality of the film was influenced by the temperature of deposition and addition of SiC composite film to the precursor ratio.…”
Section: Common Deposition Methods Of Gate Oxide Filmsmentioning
confidence: 99%